Fuzzy control algorithm for educational light tracking system - Abdul Kareem, Samir A.; Muhida, Rizah; Akmeliawati, Rini (2010)
A novel two degree of freedom (DOF) intelligent light tracking system using fuzzy logic control is presented in this paper. The fuzzy control algorithm for light tracking system is implemented using a webcamera as a vision sensor, two PC sound cards as output signal controller, and two DC motors as a pan-tilt driver mechanism. Two Fuzzy logic controllers are designed to control the camera panel angles of the proposed light tracking system. The fuzzy controller input parameters (light source pixel coordinate) and output parameters (variation of duty cycle) are used to generate the optimal pulse-width modulated (PWM) under different operating conditions to drive the motors. The motors will react accordingly when they receive signal from the sound card t o make sure the camera always focuses on the centroid of the light source. The major issues addressed in this paper are reducing the number of pulses that are sending through sound cards to move the motors, this will significantly reduce the power consumption required to drive the camera panel to the desired location. Also using a webcamera and a sound card reduces the circuitry required when compared with conventional light tracking systems, hence, saving components such as xPC target, Encoder, Tachometer, ADC or DCA and others. The system tested a t different locations. The data which were obtained by experiment were able to show a validity of the proposed controller.